Peningkatan Kompetensi Digital Marketing Siswa SMK Muhammadiyah Imogiri dalam Penerapan Teknik Copywriting dan Desain Konten - Ferdiansyah, Pramudhita; Subektiningsih; Wulandari, Irma Rofni; Anggun Anindya Sekarningrum; Devi Wening Astari; Rini Indrayani (Nawadeepa: Jurnal Pengabdian Masyarakat, 2023)
The mission of SMK Muhammadiyah Imogiri is to implement active, effective, and fun learning. SMK Muhammadiyah Imogiri organizes a "Basic Entrepreneurship and Digital Marketing Workshop" school program to improve student competence and foster an entrepreneurial spirit. The workshop material focuses on applying digital marketing techniques, namely content design and copywriting techniques. The workshop participants were 102 SMK Muhammadiyah Imogiri School students. The implementation of the workshop consists of several parts, namely starting with a pre-test, presentation of the material, practice, and ending with a post-test. Evaluation is carried out using a pre-test and post-test based on five aspects, namely the aspect of measuring students' views on the importance of content editing, the level of optimization of content editing using Canva, the importance of analysis and selecting hashtags according to published content, the application of copywriting techniques to create appropriate captions according to the content posted on Instagram, and when measuring students' level of competency or knowledge about digital marketing, there was an increase in knowledge transfer of 48.1%. Based on these aspects, the average increase in the five aspects was 28.24%, with 102 students participating in the training.